2020
DOI: 10.4103/jcd.jcd_601_20
|View full text |Cite
|
Sign up to set email alerts
|

Conservative shaping combined with three-dimensional cleaning can be a powerful tool: Case series

Abstract: Conservative endodontics has been introduced about a decade ago. Since then, it has been demonstrated that less canal preparations lead to more dentin preservation resulted in decreased stress on tooth structure, mainly in the coronal third of the root, and potentially a higher resistance to fracture. In addition, smaller and larger canal preparations were comparable with regard to the cleanliness of the root canal. The purpose of this case series was to report on the outcome of root canal treatments following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…The treatment of choice is root canal therapy. The main aim of this therapy is to remove bacteria and infected materials from the pulp and periapical tissues and replace them with biocompatible material [ 2 , 3 , 4 ]. According to Siqueira JF et al and Lin LM et al, complex root anatomy is the primary cause of endodontic treatment failure [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of choice is root canal therapy. The main aim of this therapy is to remove bacteria and infected materials from the pulp and periapical tissues and replace them with biocompatible material [ 2 , 3 , 4 ]. According to Siqueira JF et al and Lin LM et al, complex root anatomy is the primary cause of endodontic treatment failure [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that conservative shaping can achieve excellent results when performed in conjunction with active cleaning [11,12,[14][15][16][17][18]. The shaping with rotating files with conicity and low diameters associated with a powerful cleaning leads to cleaning the dentinal walls and leads the irrigants to easily reach the lateral anatomies, including the dentinal tubules [9,19].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it also includes, as established by numerous clinical and histological studies, particular areas that are challenging to access or even inaccessible (isthmuses, loops, lateral canals, ramifications, deltas, and dentinal tubules). [ 5 6 7 8 ] Consequently, mechanical shaping cannot access all areas of the complex endodontic system, regardless of the technique used, leaving parts of the root canals untreated. [ 9 ] Therefore, it is crucial to perform endodontic biochemical cleaning (accessible and inaccessible areas).…”
Section: Introductionmentioning
confidence: 99%